Shifted magnetic alignment in vertebrates: Evidence for neural lateralization? - Malkemper, E Pascal; Painter, Michael S; Landler, Lukas (Journal of theoretical biology, 2016)
A wealth of evidence provides support for magnetic alignment (MA) behavior in a variety of disparate species within the animal kingdom, in which an animal, or a group of animals, show a tendency to align the body axis in a consistent orientation relative to the geomagnetic field lines. Interestingly, among vertebrates, MA typically coincides with the north-south magnetic axis, however, the mean directional preferences of an individual or group of organisms is often rotated clockwise from the north-south axis. We hypothesize that this shift is not a coincidence, and future studies of this subtle, yet consistent phenomenon may help to reveal some properties of the underlying sensory or processing mechanisms, that, to date, are not well understood. Furthermore, characterizing the fine structure exhibited in MA behaviors may provide key insights to the biophysical substrates mediating magnetoreception in vertebrates. Therefore, in order to determine if a consistent shift is exhibited in taxonomically diverse vertebrates, we performed a meta-analysis on published MA datasets from 23 vertebrate species that exhibited an axial north-south preference. This analysis revealed a significant clockwise shift from the north-south magnetic axis. We summarize and discuss possible competing hypotheses regarding the proximate mechanisms underlying the clockwise shifted MA and conclude that the most likely cause of such a shift would be a lateralization in central processing of magnetic information.
Keywords: Lateralization; druhová specificita; Functional Laterality; Magnetoreception; obratlovci; Geomagnetic field; Orientation; Central sensory processing; magnetické jevy; Vertebrates; zvířata; Spatial orientation; funkční lateralita; orientace; Cortical hemispheres; Species Specificity; Magnetic alignment; Animals; Magnetic Phenomena